Morphometric characterization of the mesoamerican slider (trachemys venusta, emydidae) from the atrato river basin, colombia. (2014)
A group of 89 sliders, Trachemys venusta, were confiscated by the local authorities in the Atrato river basin of Colombia. The life history of this species has known from populations in different countries but in Colombia there is only one anecdotic report that is 50 years old. Given the wide biogeography and diversity of forms of this species throughout its range from Mexico to Colombia, we report this case of turtle confiscation and use this opportunity to document the morphometry that this taxa achieves in this region of Colombia. We underscore an urgent need for further studies using individuals indigenous to Colombia to better understand the phylogenetic relationship of T. venusta throughout its distributional range.Caracterización Morfométrica de la Hicotea Mesoamericana (Trachemys venusta, Emydidae) en la Cuenca del río Atrato, Colombia.     Un grupo de 89 hicoteas mesoamericanas, Trachemys venusta, fueron decomisados por las autoridades locales en la cuenca del río Atrato de Colombia. La historia de vida de esta especie ha sido estudiada usando poblaciones de diferentes países en su distribución, sin embargo de Colombia sólo existe un reporte anecdótico escrito hace más de 50 años. Dada la amplia distribución geográfica de esta especie en su rango de distribución desde México hasta Colombia, y la gran variedad de fenotipos de esta especie, nosotros reportados este caso de decomiso de tortugas hicoteas y documentamos su morfometría comparando con lo reportado para esta especie en otros países. Resaltamos la urgencia de realizar estudios de esta especie que incluyan especímenes nativos de Colombia para comprender relaciones filogenéticas de T. venusta en todo su rango de distribución.